Importance of genetic sequencing studies in managing chronic neonatal diarrhea: a case report of a novel variant in the glucose–galactose transporter SLC5A1 - López-Mejía, Lizbeth; Guillén-Lopez, Sara; Vela-Amieva, Marcela; Santillán-Martínez, Rosalía; Abreu, Melania; González-Herrra, María Dolores; Díaz-Martínez, Rubicel; Reyes-Magaña, Juan Gaspar (Frontiers in Pediatrics, 2024)
Introduction: Congenital glucose-galactose malabsorption (CGGM) is a rare autosomal recessive disorder that primarily causes chronic intractable diarrhea. This study aims to describe the clinical history, laboratory profile, diagnostic workflow, and management of the first patient reported with CGGM in Mexico. Methods: The case involves a Mexican female infant with recurrent admissions to the emergency room since birth due to chronic diarrhea. Results: The infant was born at term by C-section with a birth weight of 3.120 kg and height of 48 cm from consanguineous parents. She had been breast-fed until day 5 of her life when she presented lethargy, diarrhea, abdominal discomfort, and jaundice. During the first evaluation at the emergency room, the significant laboratory finding was blood tyrosine elevation; afterward, amino acid and succinyl acetone determinations were obtained, discarding tyrosinemia. When admitted to the hospital, an abdominal USG detected a double kidney collecting system. At this time, rice formula was introduced to the patient. She was discharged with jaundice improvement, but diarrhea persisted. Several formula changes had been made from rice to extensively hydrolyzed casein protein to whey-based, with no clinical improvement; the patient still had 10-12 excretions daily. In the second hospitalization, the patient presented anemia, severe dehydration, hyperammonemia, and renal tubular acidosis. The geneticist performed a next-generation sequencing panel for inborn errors of metabolism and congenital diarrhea, identifying a homozygous variant in SLC5A1 (c.1667T>C). The diagnosis of CGGM was made at three months of age. The infant was initially treated with a modular galactose-glucose-free formula with oil, fructose, casein, minerals, and vitamins until a commercial fructose-based formula was introduced. This led to a complete resolution of diarrhea and improved nutritional status. Discussion: Diagnosing CGGM is challenging for clinicians, and next-generation sequencing is a valuable tool for providing appropriate treatment. More detailed information on patients with this condition might lead to possible phenotype-genotype correlations. This case's primary clinical and biochemical findings were chronic diarrhea, anemia, jaundice, renal tubular acidosis, hyperammonemia, and initial hypertyrosinemia. Symptoms were resolved entirely with the fructose-based formula.